Extracellular Trap Formation in Response to Trypanosoma cruzi Infection in Granulocytes Isolated From Dogs and Common Opossums, Natural Reservoir Hosts - de Buhr, Nicole; Bonilla, Marta C.; Jimenez-Soto, Mauricio; von Köckritz-Blickwede, Maren; Dolz, Gaby (Frontiers in Microbiology, 2018)
Granulocytes mediate the first line of defense against infectious diseases in humans as well as animals and they are well known as multitasking cells. They can mediate antimicrobial activity by different strategies depending on the pathogen they encounter. Besides phagocytosis, a key strategy against extracellular pathogens is the formation of extracellular traps (ETs). Those ETs mainly consist of DNA decorated with antimicrobial components and mediate entrapment of various pathogens. In the last years, various studies described ET formation as response to bacteria, viruses and parasites e.g. Trypanosma (T.) cruzi. Nevertheless, it is not fully understood, if ET formation helps the immune system to eliminate intracellular parasites. The goal of this study was to analyze ET formation in response to the intracellular parasite Trypanosma (T.) cruzi by granulocytes derived from animals that serve as natural reservoir. Thus, we investigated the ET formation in two T. cruzi reservoirs, namely dogs as domestic animal and common opossums (Didelphis marsupialis) as wild animal. Granulocytes were harvested from fresh blood by density gradient centrifugation and afterwards incubated with T. cruzi. We conducted the analysis by determination of free DNA and immunofluorescence microscopy. Using both methods, we show that T. cruzi efficiently induces ET formation in granulocytes derived from common opossum as well as dog blood. Most ETs from both animal species as response to T. cruzi are decorated with the protease neutrophil elastase. Since T. cruzi is well known to circulate over years in both analyzed animals as reservoirs, it may be assumed that T. cruzi efficiently evades ET-mediated killing in those animals. Therefore, ETs may not play a major role in efficient elimination of the pathogen from the blood of dogs or common opossums as T. cruzi survives in niches of their body. The characterization of granulocytes in various animals and humans may be helpful to understand the anti-pathogenic capacity and overall role of ETs against zoonotic pathogens like T. cruzi.